Akulturasi Tradisi Sedekah Laut di Kabupaten Cilacap Dengan Hukum Islam - Rahil Syira Roudhlotul Janah; Salsabila Phytagora Athariq; Siti Aliza Nuraini Wahdini; Yulianisa Amelia Fasya (Jurnal Budi Pekerti Agama Islam, 2024)
This article discusses the tradition of sea alms in Cilacap Regency and how this tradition is acculturated with Islamic teachings. Sedekah laut is a traditional ceremony performed by coastal communities as a form of gratitude for sustenance from the sea. This tradition originally contained elements that were considered deviant from Islamic teachings, such as offerings to the sea spirit Kanjeng Ratu Kidul. However, through acculturation, these elements have been adapted to Islamic values, so that they now involve prayers and alms to Allah SWT. The sea alms tradition also plays a role in strengthening the spirit of mutual cooperation and awareness of cultural preservation among coastal communities. This research uses a descriptive qualitative method with a literature study to examine the relationship between customary law and Islamic law in this tradition. The results show that customary law and Islamic law can interact harmoniously without dominating each other, each having a role in preserving local traditions that enrich Indonesia's cultural heritage.